(untitled) (Philology, 2026)
The aim of the presented paper is to analyze the linguistic realization of the binary opposition self-other in the fixed comparisons in two unrelated languages, Bulgarian and French, and to track the general and the specific in the idea and assessment of the two polar concepts. Of particular research interest is the crossing of ethnical stereotypes that reflect the concept of other in the fixed comparisons with the component of the ethnonym in Bulgarian and French. The drawn conclusions concern the representation of the concepts self-other in the fixed comparison in the two languages and the specific assessment expressed by the latter, as a result of the ideology of the respective linguistic community.